Neuroprotective Effects of Genistein in Mongolian Gerbils: Estrogen Receptor-β Involvement - Andrea Donzelli; Daniela Braida; Annamaria Finardi; Valeria Capurro; Anna Elisa Valsecchi; Mariapia Colleoni; Mariaelvina Sala (Elsevier, 2010)
Genistein is a naturally occurring plant-derived phytoestrogen, present in the human diet, known to possess some beneficial effects. The present study investigated the effect of genistein on neuroprotection evaluated through electroencephalographic and behavioural correlates in a model of global cerebral ischemia in gerbils. Over the dose range tested, genistein (3 and 10 mg/ kg), given 5 min after recirculation antagonized the ischemia-induced electroencephalographic total spectral power decrease 7 days after ischemia; fully prevented ischemia-induced hyperlocomotion evaluated 1 day after ischemia; reversed ischemia-induced memory impairment evaluated through both nest building behaviour and object recognition test; decreased malondialdehyde overproduction in the brain, evaluated 7 days after reperfusion; and fully promoted the survival of pyramidal cells in the CA1 hippocampal subfield. The selective antagonist for estrogen receptor-β (ERβ), 4-[2-phenyl-5,7-bis(trifluoromethyl) pyrazolo[1,5-a]pyrimidin-3-yl]phenol (PHTPP) given 30 min before carotid occlusion, fully prevented the neuroprotective effect of genistein at the dose of 3 mg/kg. These results demonstrate the neuroprotective effect of genistein through the activation of ERβ and provide further grounds for the growing interest concerning the true potential of phytoestrogens as compounds to beneficially affect brain injury without having the disadvantages of estrogens. Keywords:: ischemia, electroencephalography (EEG), phytoestrogen, CA1, estrogen receptor-β